2017
DOI: 10.1002/ejlt.201700133
|View full text |Cite
|
Sign up to set email alerts
|

Efficient microwave‐assisted synthesis of glycerol monodecanoate

Abstract: International audienceSolvent-free microwave-assisted synthesis was carried out to prepare 2,3-dihydroxypropyl decanoate, by esterification of decanoic acid in the presence of two distinct glycerol derivatives, glycidol, and glycerol carbonate, respectively. The process described is based on microwaves heating source with electrical power in the range of 200–400 W, involving stoichiometric proportions of decanoic acid and glycerol derivatives, and using catalytic amounts of TBAI used as organocatalyst. Convers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The process uses microwave irradiation with an output power of 200-400 W, involving decanoic acid and glycerol derivatives (stoichiometric proportions), with an organo-catalyst. The microwave-assisted synthesis notably enhances the selectivity in 2,3-dihydroxypropyl decanoate (at 300 W, 91%), reinforcing the efficiency and selectivity of the microwave-assisted method [93].…”
Section: Microwave Assisted Conversion Of Glycerol/glycerol Derivatives To Organic Carbonatesmentioning
confidence: 65%
“…The process uses microwave irradiation with an output power of 200-400 W, involving decanoic acid and glycerol derivatives (stoichiometric proportions), with an organo-catalyst. The microwave-assisted synthesis notably enhances the selectivity in 2,3-dihydroxypropyl decanoate (at 300 W, 91%), reinforcing the efficiency and selectivity of the microwave-assisted method [93].…”
Section: Microwave Assisted Conversion Of Glycerol/glycerol Derivatives To Organic Carbonatesmentioning
confidence: 65%
“…To improve and optimize 2,3-dihydroxypropyl decanoate synthesis, Mhanna et al reported the MW-assisted solvent-free esterification of decanoic acid in the presence of two distinct derivatives of glycerol 3 , glycidol 5 and glycerol carbonate 6 . 80 In both cases, the rates of conversion and selectivity were increased when compared to conventional heating procedures. The described process was based on a MW heating source with electrical power in the range of 200–400 W, involving stoichiometric proportions of decanoic acid and glycerol derivatives 5 and 6 , and using catalytic amounts of tetra-butylammonium iodide as an organocatalyst.…”
Section: Microwaves-assisted Catalysis For the Production Of Glycerol...mentioning
confidence: 97%